Psychological Distress Among the U.S. General Population During the COVID-19 Pandemic - Guerrini, Christi J.; Schneider, Sophie C.; Guzick, Andrew G.; Amos Nwankwo, Gifty N.; Canfield, Isabel; Fedson, Savitri; Gutierrez, Amanda M.; Sheu, Jessica C.; Song, Amber Y.; Villagran, Alexandra M.; McGuire, Amy L.; Storch, Eric A. (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic is taking a significant global toll on emotional well-being, but evidence of mental health impacts in the United States remains limited. In April 2020, we conducted an exploratory survey of U.S. residents to understand prevalence of and factors associated with psychological distress during the pandemic. Data collection was conducted using Qualtrics, an online survey platform, and U.S. adult respondents were recruited via Amazon’s Mechanical Turk platform. Among 1,366 respondents, 42% (n=571) reported clinically significant anxiety and 38% (n=519) reported clinically significant depression. Factors associated with anxiety and depressive symptoms included Hispanic/Latino ethnicity; younger age; lower income; employment or living with a health care worker-first responder; caregiver status; SARS-CoV-2 infection status; decreased frequency of engagement in healthy behaviors; and changed frequency of engagement in unhealthy behaviors. That some of these factors are associated with elevated distress during the pandemic is not yet widely appreciated and might be useful in informing management of mental health care resources.